The Role of Local Government In Protection of Copyright Against Creative Industry Local Cultural Heritage In Sawahlunto City - Rifqi Dewi Lawra; Yulia Nizwana (Yustisia, 2017)
Intellectual Property Rights (IPR) Â are closely related to the economic growth of a State. Appreciation and protection of intellectual works will create a conducive climate for the creativity and innovation of the people. IPR is a Right that is closely related to economic issues. IPR is identical with the commercialization of intellectual works. The commercialization of intellectual works in principle aims to generate economic benefits. Traditionally intellectual property is divided into two branches of "Industrial wealth" and "Copyright". Industrial Property includes the protection of the invention through a Patent, certain commercial protection through the laws of the mark and the laws of industrial design protection. In addition, industrial wealth includes unfair competition control. Traditional Knowledge as a Regional Asset that obtains Legal Protection, As set forth in the copyright law, in Article 10 paragraphs (1) and (2). The professional entity that has the right to decide may not be the copyright registration Copyright is an institution of IPR in each region and Higher Education. Such as the District and Municipal Trade Office, Provincial Trade Office as an extension of the Directorate General of IPR in Jakarta. Sawahlunto city is one of the cities in the province of West Sumatra Indonesia. Currently, the city of Sawahlunto develops into a multi ethnic old tourist city, making it one of the best old cities in Indonesia. The result of crafts from the work of the creation of the traditional community of Silungkang city of Sawahlunto is a cultural asset that needs to be protected under the Copyright Act. To get legal protection against the copyrights of the local creative industry heritage, is inseparable from the role of local government of course, where expected with the problems faced by the public to obtain legal protection of their copyrights. The purpose of this study is to know how the role of local government in the protection of copyright to the creative industry of local cultural heritage in Sawahlunto city, and what are the constraints of local government in the protection of copyright to the creative industry of local cultural heritage in Sawahlunto city. The object of this study is to see how far the role of local government in the protection of copyright to the creative industry of local cultural heritage in Sawahlunto city. To obtain primary data from respondents, this research will use semi-structured interview method